Cardiovascular disease risk in Korean patients with systemic lupus erythematosus compared to diabetes mellitus and the general population - Jung-Yong Han; Soo-Kyung Cho; Yena Jeon; Gaeun Kang; Sun-Young Jung; Eun Jin Jang; Yoon-Kyoung Sung (Scientific Reports)
Abstract To evaluate the incidence and risk of cardiovascular disease (CVD) among Korean patients with systemic lupus erythematosus (SLE) comparing them to diabetes patients and the general population. This nationwide cohort study focused on incident SLE patients aged over 40 years, matched with diabetes patients and the general population (1:4:4 ratio). CVD was defined as ischaemic heart disease, ischaemic stroke, and cardiac arrest. Incidence rate and incidence rate ratio (IRR) of CVD were calculated using generalised estimating equation models. The Fine-Gray model assessed risk factors for CVD in both SLE and diabetes patients. The study included 4272 incident SLE patients, 17,003 diabetes patients, and 17,088 from the general population. SLE patients had higher CVD risk compared to the general population, with adjusted IRRs of 1.99 for overall CVD. Diabetes patients showed increased CVD risk, but to a lesser extent, with an IRR of 1.39. SLE patients aged 40–59 years displayed a significantly elevated CVD risk. Advanced age, male gender, and current use of glucocorticoids, immunosuppressive, and anti-platelet agents were associated with increased CVD risk in SLE patients. SLE patients have a higher risk of CVD compared to the general population, more so than diabetes patients.